Fabrication, degradation behavior and cytotoxicity of nanostructured hardystonite and titania/hardystonite coatings on Mg alloys. (July 2016) - Bakhsheshi-Rad, H.R.; Hamzah, E.; Kasiri-Asgarani, M.; Jabbarzare, S.; Daroonparvar, M.; Najafinezhad, A.
Abstract: In this study, nanostructured hardystonite (HT) and titania (TiO2 )/hardystonite (HT) dual-layered coatings were deposited on biodegradable MgCaZn alloy via physical vapor deposition (PVD) combined with electrophoretic deposition (EPD). Although a single layer nano-HT coating can decrease the corrosion rate from 1.68 to 1.02 mm/year, due to the presence of porosities and microcracks, the nano-HT layer cannot sufficiently protect the Mg substrate. In contrast, the corrosion resistance of nano-HT coating is further improved by using nano-TiO2 underlayer since it was a smooth, very uniform and compact layer with higher contact angle (52.30°). In addition, the MTT assay showed the viability of MC3T3-E1 on the nano-HT and nano-TiO2 /HT coatings. The results demonstrated that the two-step surface modification improved both corrosion resistance and the cytocompatibility of the Mg alloy, hence making it feasible for orthopedic applications. Highlights: A novel nano-TiO2 /HT duplex coating was deposited on Mg alloy. Morphology and structure of nano-HT and nano-TiO2 /HT coatings were evaluated. Cytotoxicity of uncoated Mg alloy, nano-HT and TiO2 /HT coatings were investigated. The duplex coating significantly increased the corrosion resistance of Mg alloy.